AROMATERAPI TERHADAP PENGURANGAN MUAL MUNTAH PADA IBU HAMIL - Husna, Febby Yolanda; Aini, Al; Yunisa, Natia; br Sianturi, Ecy Anjelina (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Nausea and vomiting is an uncomfortable condition that is usually felt in 50% of mothers who are experiencing pregnancy, which usually occurs in the early trimester. One of them is in the management to reduce pharmacological therapy by providing aromatherapy. The purpose of this study or research is to find out whether the impact of giving an aromatherapy can reduce nausea or vomiting for pregnant women in the first trimester or earlier. The purpose of this writing is to be able to find out various kinds of complementary therapies with an evidence base and based on evidence based that can reduce vomiting and nausea during pregnancy. Based on the description above, the authors carried out this literature study on research that could be related to complementary therapy in reducing nausea and vomiting during pregnancy. This study also shows that there is an effect in giving this aromatherapy to relieve the effects of vomiting and nausea in pregnant women in the first trimester. In the provision of this aromatherapy can be used when reducing nausea and vomiting in pregnant women can affect the nerves in the hypothalamus can relieve nausea and vomiting.